Effects of COVID-19 Lockdown on Movement Disorders Patients With Deep Brain Stimulation: A Multicenter Survey - Piano, Carla (Front Neurol, 2020)
Background: The containment measures taken by Italian government authorities during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic caused the interruption of neurological activities of outpatient clinics. Vulnerable patients, as Parkinson's disease (PD) and dystonic patients with deep brain stimulation (DBS), may have an increased risk of chronic stress related to social restriction measures and may show a potential worsening of motor and psychiatric symptoms. Methods: This cross-sectional multicenter study was carried out during the SARS-CoV-2 pandemic and was based on a structured survey administered during a telephone call. The questionnaire was designed to gather motor and/or psychiatric effects of the lockdown and coronavirus disease 2019 (COVID-19) epidemiologic information in PD and dystonic patients with a functioning DBS implant. Results: One hundred four patients were included in the study, 90 affected by PD and 14 by dystonia. Forty-nine patients reported a subjective perception of worsening of global neurological symptoms (motor and/or psychiatric) related to the containment measures. In the multivariate analysis, having problems with the DBS device was the only independent predictor of motor worsening [odds ratio (OR) = 3.10 (1.22–7.91), p = 0.018]. Independent predictors of psychiatric worsening were instrumental activities of daily living (IADL) score [OR = 0.78 (0.64–0.95), p = 0.012] and problems with DBS [OR = 5.69 (1.95–16.62), p = 0.001]. Only one patient underwent nasopharyngeal swabs, both negative, and no patient received a diagnosis of COVID-19. Conclusions: Lockdown restriction measures were associated with subjective worsening of motor and psychiatric symptoms in PD and dystonic patients treated with DBS, and they may have exacerbated the burden of neurological disease and increased the chronic stress related to the DBS management.